Pengaruh Penggunaan Qris sebagai Strategi Pembayaran Digital terhadap Kepuasaan dan Loyalitas Konsumen di Era Modern - Kamelya Dewanti; Dini Amanda; Fabian Alichsan; Indah Noviyanti (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to evaluate the impact of using QRIS (Quick Response Code Indonesian Standard) as a digital payment strategy on consumer satisfaction and loyalty in the modern era. QRIS is a practical solution in payment transactions in various business sectors, especially in facing technological developments and changes in consumer behavior. The approach to this study is quantitative using a survey method to consumers who transact in various businesses that have implemented the QRIS system. Data were collected through questionnaires and analyzed using a simple linear regression method. The research findings show that the use of QRIS has a positive effect on consumer satisfaction, which in turn contributes to increasing consumer loyalty. The ease, speed, and security of transactions offered by QRIS have been shown to improve customer experience, thereby strengthening their relationship with the business. The results of this study emphasize the importance of implementing QRIS as part of an effective digital payment strategy in increasing consumer satisfaction and loyalty in the digital era.